Synonymous substitution rates predict HIV disease progression as a result of underlying replication dynamics - Lemey, Philippe (2015)
Upon HIV transmission, some patients develop AIDS in only a few months, while others remain disease free for 20 or more years. This variation in the rate of disease progression is poorly understood and has been attributed to host genetics, host immune res